Dihydroartemisinin-Transferrin Adducts Enhance TRAIL-Induced Apoptosis in Triple-Negative Breast Cancer in a P53-Independent and ROS-Dependent Manner - Zhou, Xinyu; Soto-Gamez, Abel; Nijdam, Fleur; Setroikromo, Rita; Quax, Wim J. (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) is a highly aggressive breast cancer subtype independent of estrogen receptor, progesterone receptor, or human epidermal growth factor receptor 2. It has a poor prognosis and high recurrence. Due to its limited treatment options in the clinic, novel therapies are urgently needed. Single treatment with the death receptor ligand TRAIL was shown to be poorly effective. Recently, we have shown that artemisinin derivatives enhance TRAIL-induced apoptosis in colon cancer cells. Here, we utilized transferrin (TF) to enhance the effectiveness of dihydroartemisinin (DHA) in inducing cell death in TNBC cell lines (MDA-MB-231, MDA-MB-436, MDA-MB-468 and BT549). We found that the combination of DHA-TF and the death receptor 5-specific TRAIL variant DHER leads to an increase in DR5 expression in all four TNBC cell lines, while higher cytotoxicity was observed in MDA-MB-231, and MDA-MB-436. All the data point to the finding that DHA-TF stimulates cell death in TNBC cells, while the combination of DHA-TF with TRAIL variants will trigger more cell death in TRAIL-sensitive cells. Overall, DHA-TF in combination with TRAIL variants represents a potential novel combination therapy for triple-negative breast cancer.